The Interaction Patterns of Teachers and Students in Islamic Religion Education lesson on Online Class at Plandaan Senior High School Jombang - Hidayatur Rohmah; Afyan Viki Pratama (SCHOOLAR: Social and Literature Study in Education, 2022)
In the Covid 19 era, learning became online, so the learning process was carried out online. The objectives of the researcher are: 1) Knowing the pattern of interaction between teachers and students, during online learning 2.) Knowing the supporting and inhibiting factors during the online learning process 3.) Overcoming obstacles during the online learning process. This study uses a qualitative descriptive method which is applied at SMA Negeri Plandaan Jombang class XI Mapel PAI which consists of 30 students. The results showed that during the online learning process, the teacher used whatshap media and PPT groups. Learning goes well, and is more effective, and students can follow the lesson well. The supporting factor is the aid package from the government and schools. inhibiting factor in this study in terms of the network when collecting assignments. In overcoming this, the teacher prioritizes coaching and directing students to stay enthusiastic in the online learning process.